Pilot-scale continuous flow granular reactor for the treatment of extremely low-strength recirculating aquaculture system wastewater. Issue 2 (April 2022) - Santorio, S.; Val del Rio, A.; Amorim, C.L.; Arregui, L.; Castro, P.M.L.; Mosquera-Corral, A.
Abstract: To avoid toxic ammonium and nitrite concentrations in aquaculture systems is crucial to maintain the fish production. When recirculating aquaculture systems (RAS) operate in freshwater farms during the dry seasons, the concentrations of these pollutants increase. The objective of the present study is the evaluation of a Continuous Flow Granular Reactor (CFGR) for the treatment of freshwater RAS stream at pilot-scale during two consecutive dry seasons. The CFGR was fed with a extremely low-strength recirculation stream of a trout farm (0.12–1.84 mg NH4 + -N/L and 2.2–8.14 mg C/L). Two different configurations were evaluated. The first configuration consisted on a CFGR fed from the bottom, being the up-flow velocity the only shear force to mix the biomass. The second configuration incorporated a mechanical stirrer and a sieve to improve the biomass mixing and retention. The CFGR was operated at short hydraulic retention times (HRT) which ranged from 11 to 68 min. The configuration with a mechanical stirrer and sieve was optimal in terms of biomass retention and nitrogen removal performance. Despite the low nitrogen and organic matter concentrations, granulation was achieved in 55 days, with an average granule diameter up to 0.47 mm. Ammonium and nitrite removal percentages up to 81% and 100% were achieved, respectively. The ammonium and nitrite production rate in the trout farm were lower than the removal achieved by the CFGR, which makes the implementation of this system appropriated to maintain the concentration of these compounds below toxic levels for rainbow trout. Graphical Abstract: ga1 Highlights: Granulation with low-strength aquaculture effluent < 2 mg N/L and low HRT < 70 min. Ammonium and nitrite removals were up to 81% and 100%, respectively. Treated effluent had ammonium and nitrite concentrations under toxic levels for fish. The use of mechanical stirring and a sieve on the top was the optimal configuration. Complete nitrification was the main biological process in the granular pilot-plant.